Banthưk phūmpanyā phalittaphan OTOP dīdēn Čhangwat ʻUbon Rātchathānī (Samnakngān Khana ʻAnukammakān Nưng Tambon Nưng Phalittaphan Čhangwat ʻUbon Rātchathānī, Samnakngān Phatthanā Chumchon Čhangwat ʻUbon Rātchathānī, 2005)
Background and production process of excellent OTOP products, one tambon one product, of Ubon Ratchathani Province, Northeastern Thailand.